Cross Coupling Control Strategy of Two Motors for Position Synchronization - ZHU Bo; ZHANG Yu-peng; XU Pan-teng; SONG Shu-bo; JIAO Shi; ZHENG Xing-xing (Journal of Harbin University of Science and Technology)
Double-break high speed switch is the important equipment for the EHV transmission system， but the motor control system of the switch cannot satisfy the synchronous requirements. In order to solve the synchronous error problem of the double motors system， based on cross-coupled control， an improved cooperative control strategy of double motors is proposed. Firstly， the coupling relation between the speed and position of the two motors was established based on the cross-coupling principle， and the motion error of the two motors was compensated quickly by the synchronous compensator. Secondly， a moving average filter is designed for the harmonics of the observed signal. Finally， the simulation model of the double motors control system is built. The simulation results show that when the system is disturbed by load， the proposed control strategy can reduce the speed error of the double motors， realize the synchronous operation of the double motors， and reduce the action difference between the double motors.